Faktor Risiko Hepatitis B pada Ibu Hamil di Kota Semarang Tahun 2020-2021 (Studi Kasus di Puskesmas Genuk & Puskesmas Bangetayu) - Raina Khairana Denando; Widya Hary Cahyati (Jurnal Kesehatan Masyarakat, 2022)
Hepatitis B virus is a blood-borne pathogen that causes hepatitis B. Data from Semarang City Health Office showed that there were 359 and 181 cases of hepatitis B in pregnant women in 2020 and 2021. Genuk Public Health Center and Bangetayu Public Health Center have been in the top ten highest cases for two years in a row. The purpose is to determine the risk factors for the incidence of hepatitis B in pregnant women in the working area of Genuk Public Health Center and Bangetayu Public Health Center, Semarang City in 2020-2021. The type of research is observational analytical methods with case-control approach. This study used purposive sampling technique with sample size of 61 cases and 61 controls. The data analysis used is univariate, bivariate, and multivariate. Processing data using Chi-Square, Fisher, and logistic regression. The results showed that there is a relationship between parity (p=0.000), education level (p=0.025), age at first marriage (p=0.007), frequency of spouse's marriage (p=0.008), spouses’s hepatitis B status (p=0.001), history of spouse’s mobility (p=0.007), family history of hepatitis B (p=001), and history of needle use (p=0.013) with the incidence of hepatitis B in pregnant women. The suggestions are implementation of counseling on early marriage, family planning education, and strengthening surveillance and monitoring.